Doses de nitrogênio em cobertura no feijoeiro em sucessão a gramíneas no cultivo de inverno-primavera - Amaral, Camila Baptista do [UNESP] (2014)
The common bean has been explored in different management systems, with emphasis on no-tillage system, since it presents interesting agronomic and commercial characteristics. In tropical regions, however, the greatest difficulty for success in this system is the maintenance of the straw, because of the high rate of decomposition in these regions. For this reason, species of high C/N ratio are the most suitable to render the management system with the common bean, such as corn and brachiaria. However, more attention should be given to nitrogen fertilization, due immobilization process that can occur in no-tillage system. Thus, the aim of this study was to evaluate the influence of topdressed nitrogen fertilization on the irrigated common bean in succession with maize and brachiaria, in single or intercropped grown, under no-tillage system. The experiment was conducted in eutrophic red latosol, loam texture, in split plot design with three replications. The plots consisted of: M + F) exclusive maize in summer and common bean in winter - spring, MB + F ) of maize intercropped with brachiaria in summer and common bean in winter - spring and B + F ) exclusive brachiaria in summer and common bean winter - spring. The subplots consisted of four topdressed rates of nitrogen, corresponding to 40, 80, 120 and 160 kg ha-1 of N and a witness that was omitted the nitrogen fertilization. Agronomic characteristics of maize (exclusive and intercropped) were evaluated, such as characteristics of the straw of the predecessor crop and agronomic and technological quality of the common bean crop. Intercropped brachiaria does not affect the characteristics of maize, compared to exclusive grown. When grown after brachiaria, the common bean have the highest yield (exclusive brachiaria bean in summer and in winter - spring). In all management systems, 136 kg ha-1 of nitrogen gave the maximum yield, mainly influenced by ...